Decreased susceptibility to lipid peroxidation of Goto-Kakizaki rats: Relationship to mitochondrial antioxidant capacity - Ferreira, F. M. L. (1999)
The respiratory function and the antioxidant capacity of liver mitochondrial preparations isolated from Goto-Kakizaki non-insulin dependent diabetic rats and from Wistar control rats, with the age of 6 months, were compared. It was found that Goto-Kakizaki mitochondrial preparations presented a higher coupling between oxidative and phosphorylative systems, compared to non-diabetic preparations. Goto-Kakizaki mitochondria presented a lower susceptibility to lipid peroxidation induced by ADP/Fe2+, as evaluated by the formation of thiobarbituric acid substances. The decreased susceptibility to peroxidation in diabetic rats was correlated with an increase in mitochondrial vitamin E ([alpha]-tocopherol) content and GSH/GSSG ratio. Moreover, the glutathione reductase activity was significantly increased, whereas the glutathione peroxidase was decreased. Superoxide dismutase activity was unchanged in diabetic rats. Fatty acid analyses showed that the content in polyunsaturated fatty acids of Goto-Kakizaki mitochondrial membranes was significantly higher compared to controls. These results indicate that the lower susceptibility to lipid peroxidation of mitochondria from diabetic rats was related to their antioxidant defense systems, and may correspond to an adaptative response of the cells against oxidative stress in the early phase of diabetes.